Physical and Emotional Sibling Violence in Childhood and Attachment in Close Relationships in Adulthood - Perkins, Nathan H. (Journal of interpersonal violence, 2023)
Despite the consequences of physical and emotional sibling violence, which can last into adulthood, research examining this form of family violence is minimal compared to child abuse, interpartner violence, and elder abuse. One area that has received scarce attention is the connection between physical and emotional sibling violence and attachment in close relationships in adulthood. This research study examines the association between physical and emotional sibling violence and adulthood attachment in a sample of 2,458 individuals who completed a survey on the sub-Reddit platform “/r/SampleSize: Where your opinions actually matter!” Participants completed items on demographics, frequency of physical and emotional behaviors experienced with a sibling in childhood, and adult attachment. Results found physical and emotional sibling violence in childhood to be associated with attachment in close relationships in adulthood. Frequency of physical and emotional sibling violence in childhood was also associated with comfortability with intimacy and closeness, comfortability of depending and relying on others, and concerns of abandonment and rejection by others in adulthood. The findings underscore the need to not only include physical and emotional sibling violence in future research on attachment but also to examine the connection between these phenomena in diverse samples (ethnicity, sexual orientation). Also highlighted is the need for practitioners to assess sibling relationships when working with children, families, and adults experiencing attachment issues throughout the life course.